(untitled) (Community Based Medical Journal, 2013)
A study of 72 cases of uterine rupture out of total 5984 deliveries(including 3619 caesarean sections) over 1 year (from Sep. 2006 to Aug 2007) in the dept. of Obstetrics and Gynaecology, Mymensingh Medical College Hospital was reported. This gives an incidence of uterine rupture 1: 83. The results showed that, this was a common obstetric emergency & was a major cause of maternal & foetal deaths. Study showed that, 87.5% came from rural areas where facility was not available, 79% were of poor socio-economic condition .All rupture uterus cases (100%)was house wife. Peak age was between 20-30 years (68%). Among all rupture cases, 72.22% cases were between gravida 2nd to 4th,and 19.44% cases were gravida 5th or above & only 8.33% cases were Primigravida, Most of the patients(56%) were illiterate. 46% of cases had no antenatal checkup during their pregnancies. 51.38% cases labour pain lasting>16 hours. Most of the mishandled cases (66.67%) were exposed to injudicious use of uterotonic drugs before admission. Most of the cases (38.9%) handled by untrained birth attendants. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16692 Community Based Medical Journal 2013 July: Vol.02 No 02: 9-14